Clinical evaluation of failures in removable partial dentures - Jorge, Janaina Habib [UNESP]; Quishida, Cristiane C. C. [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Giampaolo, Eunice T. [UNESP] (Nihon Univ, School Dentistry, 2012)
The aim of this clinical study was to evaluate the effects of removable partial dentures on the support tissues and changes occurring in lower tooth-supported and bilateral distal-extension dentures, 5 years after placement. The study involved analysis of a total of 53 patients who received prosthetic treatment for removable partial dentures. The patients were divided into two groups. In group 1, the patients had a completely edentulous maxilla and an edentulous area with natural teeth remaining in both the anterior and posterior regions. In group 2, the patients had a completely edentulous maxilla and partially edentulous mandible with preserved anterior teeth. Tooth mobility, prevalence of caries, fracture of the abutment teeth, fracture and/or deformation of the removable partial denture components and stability of the denture base were evaluated. The use of a removable partial denture increased tooth mobility, reduced the prevalence of caries, and did not cause loss or fracture of the abutments or damage to their components, when compared with the baseline. It was concluded that there was no difference between the groups as evaluated in terms of tooth mobility, prevalence of caries, loss and fracture of the abutments or damage to the components of the removable partial denture.
Keywords: removable partial denture; abutment teeth; prosthodontics; planning